Anti-inflammatory effects of olanexidine gluconate on oral epithelial cells - Takuya Nii; Hiromichi Yumoto; Katsuhiko Hirota; Yoichiro Miyake (BMC, 2019)
Abstract Background Periodontitis is a biofilm-induced chronic inflammatory condition of the periodontium. Chemokines produced by the innate and acquired immune responses play a significant role in disease progression. Reducing biofilm formation and inflammatory response caused by chemokines is vital for preventing and treating periodontitis. Previously, we observed that treatment with 0.1% olanexidine gluconate (OLG) inhibited biofilm formation on saliva-coated hydroxyapatite. This study aimed to evaluate the anti-inflammatory effect of OLG on oral epithelial cells. Methods We examined if OLG could inhibit the inflammatory responses caused by Porphyromonas gingivalis (P. gingivalis) lipopolysaccharide (LPS) and heat-killed P. gingivalis in immortalized human oral keratinocytes (RT7). Results Treatment of RT7 with non-cytotoxic OLG concentrations significantly inhibited the production of inflammatory chemokines such as interleukin 8 (IL-8), C-C motif ligand 20 (CCL20), and growth-related oncogene protein-α (GRO-α), which are stimulated by P. gingivalis LPS in a concentration-dependent manner. Moreover, the inhibitory effects were observed regardless of the treatment time with P. gingivalis LPS (6, 12, or 24 h). OLG also significantly inhibited chemokine production stimulated by heat-killed P. gingivalis. Conclusions The findings of this study suggest that treatment with OLG inhibits chronic inflammatory reactions in oral mucosal cells, such as periodontitis, caused by oral bacteria.